1991
DOI: 10.1037/0882-7974.6.2.286
|View full text |Cite
|
Sign up to set email alerts
|

Possible selves in adulthood and old age: A tale of shifting horizons.

Abstract: Young, middle-aged, and elderly adults (N= 308) evaluated themselves on 6 dimensions of psychological well-being according to present, past, future, and ideal self-assessments, "\bung and middleaged adults saw considerable improvement in themselves from the past to the present on all dimensions of well-being. The elderly, however, indicated largely a perception of stability with prior levels of functioning. Future ratings showed that the 2 younger groups expected continued gains in the years ahead, whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
394
0
21

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(456 citation statements)
references
References 20 publications
41
394
0
21
Order By: Relevance
“…a lateral comparison) should therefore be the most preferred form of temporal comparison. Supporting evidence for this notion is reported by Ryff (1991); the author compared elderly, middle-aged, and young adults concerning their present and past perceptions of different dimensions of subjective well-being. She reported that the difference between present and past was quite low indicating a similarity or maintenance of prior levels in the group of the elderly whereas the younger groups perceived improvement on all dimensions.…”
Section: Motives and Effects Of Temporal Comparisonsmentioning
confidence: 82%
“…a lateral comparison) should therefore be the most preferred form of temporal comparison. Supporting evidence for this notion is reported by Ryff (1991); the author compared elderly, middle-aged, and young adults concerning their present and past perceptions of different dimensions of subjective well-being. She reported that the difference between present and past was quite low indicating a similarity or maintenance of prior levels in the group of the elderly whereas the younger groups perceived improvement on all dimensions.…”
Section: Motives and Effects Of Temporal Comparisonsmentioning
confidence: 82%
“…1 Second, there are fewer studies that combine all three types of diachronous rating, that is, past, present, and future evaluations (for exception, see, e.g., Ross & Buehler, 2001;Ryff, 1991). Mostly, there is emphasis on comparing either past or future evaluations with present self-evaluations (e.g., Conway & Ross, 1984;Cross & Markus, 1991;Ross, 1989;Wilson & Ross, 2001;Woodruff & Birren, 1972).…”
Section: Diachronicity Of Self-evaluationsmentioning
confidence: 99%
“…Similar to Ryff (1991), we used a fixed time difference, in our case 10 years ahead or back in time, to obtain diachronous ratings. This implied that the age groups were not referring to the same periods of the life span when making their judgments.…”
Section: Measures and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns estudos mostraram que as dimensões de personalidade podem estar relacionadas aos índices de resiliência e bem-estar subjetivo (Ryff, 1991;Staudinger, Marsiske & Baltes, 1993), além de desencadeamento de sintomas depressivos (Costa, McCrae & Zonderman, 1987;Costa et al, 2000;Diener & Diener, 1996;Martin, Valora & Poon, 2002;Small, Herzog, Hultsch & Dixon, 2003;Steunenberg, Beekman, Deeg & Kerkhof, 2006;Watson & Walker, 1996). O bem-estar tem sido considerado por alguns autores como sinônimo de qualidade de vida (Fleck, Chachamovich & Trentini, 2003 Existe uma relação direta entre qualidade de vida e intensidade de sintomas depressivos (Trentini, 2004).…”
unclassified